Human‐dominated land uses favour species affiliated with more extreme climates, especially in the tropics. Issue 3 (19th November 2019) - Williams, Jessica J.; Bates, Amanda E.; Newbold, Tim
Abstract : Rapid human population growth has driven conversion of land for uses such as agriculture, transportation and buildings. The removal of natural vegetation changes local climate, with human‐dominated land uses often warmer and drier than natural habitats. Yet, it remains an open question whether land‐use changes influence the composition of ecological assemblages in a direction consistent with the mechanism of local climatic change. Here, we used a global database of terrestrial vertebrates (mammals, birds, reptiles and amphibians) to test whether human‐dominated land uses systematically favour species with distinctive realised climatic niches. We 1) explored the responses of community‐average temperature and precipitation niches to different types of land use, 2) quantified the abundances of species with distinctive climatic niches across land uses and 3) tested for differences in emergent patterns in communities from tropical versus temperate latitudes. We found that, in comparison to species from undisturbed natural habitats, the average animal found in human‐altered habitats lives in areas with higher maximum and lower minimum temperatures and higher maximum and lower minimum precipitation levels. We further found that tropical assemblages diverged more strongly than temperate assemblages between natural and human‐altered habitats, possibly because tropical species are more sensitive to climatic conditions. These results strongly implicate the role of land‐use change in favouring species affiliated with more extreme climatic conditions, thus systematically reshaping the composition of terrestrial biological assemblages. Our findings have the potential to inform species' vulnerability assessments and highlight the importance of preserving local climate refugia.